A time-dependent quantum study of Li + HF(? = 1) ? LiF(??) + H - Gögtaş, Fahrettin; Balint-Kurti, Gabriel G. (My University, 1998)
Time-dependent quantum wave packet calculations are performed for a model based (two-dimensional) Li + HF(? = 1) ? LiF(??) + H reaction. The reaction probabilities for a broad range of collison energies are calculated by a single solution of the time-dependent Schrödinger equation. The calculated reaction probabilities show many sharp features as a function of energy which are ascribed to scattering resonances.